Relative performance of liability rules: Experimental evidence - Vera Angelova; Giuseppe Attanasi; Yolande Hiriart (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
We compare the performance of liability rules for managing environmental disasters when third parties are harmed and cannot always be compensated. A firm can invest in safety to reduce the likelihood of accidents. The firm's investment is unobservable to authorities. Externality and asymmetric information call for public intervention to define rules aimed at increasing prevention. We determine the investment in safety under No Liability, Strict Liability and Negligence, and compare it to the first best. Additionally, we investigate how the (dis)ability of the firm to fully cover potential damages affects the firm's behavior. An experiment tests the theoretical predictions. In line with theory, Strict Liability and Negligence are equally effective; both perform better than No Liability; investment in safety is not sensitive to the ability of the firm to compensate potential victims. In contrast with theory, prevention rates absent liability are much higher and liability is much less effective than predicted.
Keywords: D82; K13; K32; Q58; 330; Risk Regulation; Liability Rules; Incentives; Insolvency; Experiment